Observations on Public Policy Strategies Regarding Hydrogen in Chile and Uruguay - Roel, Nahuel (2024)
This study examines public policies on green hydrogen production in Chile and Uruguay, evaluating the strategic documents that outline these policies in both countries, and paying special attention to the socio-environmental consequences of the development of this industry. Green hydrogen, produced using renewable energy, has emerged as a crucial alternative for decarbonization and global energy transition. In Latin America, a region with abundant natural resources and a growing interest in this industry, it presents a significant economic opportunity but also entails considerable environmental challenges. The study, which includes a discourse analysis of relevant documents, also proposes a theoretical analysis from three perspectives: equality, justice, and emancipation. Both countries exhibit a strong export orientation and a focus on economic benefits, while also showing a high degree of optimism and a lack of attention to potential negative socio-environmental repercussions. In summary, the article calls for a reconsideration of the current institutional frameworks from three classic axes of political theory, aiming to highlight the necessity for public policies that comprehensively address the region’s socio-environmental challenges and advocate for greater academic production density from the social sciences on this topic.